Detection of antibodies and antigens for Diagnosis of Fasciola hepatica in alpacas naturally infected - Li E., Olga (2005)
The aim of this study was to standardize the indirect ELISA test for the detection of antibodies and to evaluate a coproantigen detection test (ES-78 sandwich ELISA) for the Fasciola hepatica diagnoses in alpacas. For the indirect ELISA, the excretion–secretion products (ES) were used as antigens and a peroxidasa anti IgG immunoconjugate of alpaca was obtained through protein A affinity cromatography. The detection ELISA was tested with the FASCIDIG diagnostic kit, which detects metabolics antigens using an AcM-ES78 monoclonal antibody of the IgG 2a sub class. Optical Density (OD) values between 0.075 and 1.435 were obtained using the indirect ELISA, where the cut-off point was 0.226. The positive control group animals were positive to the test with values between 0.331 and 1.435. The negative control group animals were negative to the test with values between 0.075 and 0.226. OD values between 0.060 and 1.532 were obtained using the coproantigen detection ELISA, where the cut-off point was 0.240. The positive control group animals were positive to the test with OD values between 0.244 and 1.532 and the negative control group animals were negative to the test with values between 0.060 and 0.240. The sensitivity, specificity and positive and negative predictive values were 100% for both ELISA tests. Both test can replace the coproparasitologic test. They are suitable for individual diagnosis and for herd diagnosis infections with F. hepatica. The indirect ELISA has demonstrated to be a useful and sensitive tool for the pasive fasciolosis diagnosis in alpacas. The coproantigen detection ELISA is a simple, fast and efficient method in the detection of active F. hepatica infection. Both diagnostic methods would be the most suitables techniques for sero-epidemiologic surveys in large herds under intensive grazing systems.